Touchless Modalities of Human-Computer Interaction in Hospitals: A Systematic Literature Review - de Camargo, Vinícius Paes; Balancieri, Renato; Teixeira, Heloise Manica Paris; Guerino, Guilherme Corredato (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2021)
This paper aims to identify conceptual and practical findings in new modalities of interactions in hospital settings. A Systematic Literature Review was carried out through database research and the snowballing technique. From the review, 46 papers were extracted. The reviewed literature describes the main modalities and technology issues to the medical specialty or hospital department where they are used. Results obtained can help readers identify better solutions for a specific department hospital requiring special conditions. Moreover, we identify that the touchless interface has a relevant contribution since it can be implemented with low-cost technology and provides system user interaction that is more adaptable to the hospital environment's health team activities.